1996
DOI: 10.1007/bf00284648
|View full text |Cite
|
Sign up to set email alerts
|

Specific binding of polypyrimidine tract binding protein and hnRNP A1 to HIV-1 CRS elements

Abstract: The human immunodeficiency virus (HIV) Rev and human T-cell leukemia virus (HTLV) Rex proteins regulate viral RNA processing. Both proteins act to overcome the block to viral structural gene expression, at least in part, by reversing the inhibitory effect of intronic RNA sequences, termed cis-acting repressive (CRS) sequences. Using HTLV type II (HTLV-II) as a model, we recently showed that the function of a 5' long terminal repeat (LTR) CRS correlates with in vitro binding by both polypyrimidine tract binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…We consider it likely that these and/or additional factors may facilitate INS recognition in vivo or play a role at later steps. In fact, hnRNP A1 has been shown to participate in INS function, possibly by direct interactions (9,41). The possible mechanistic roles of such factors in INS-mRNA regulation remain to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider it likely that these and/or additional factors may facilitate INS recognition in vivo or play a role at later steps. In fact, hnRNP A1 has been shown to participate in INS function, possibly by direct interactions (9,41). The possible mechanistic roles of such factors in INS-mRNA regulation remain to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Several mRNA-binding proteins, including PTB/hnRNP I, hnRNP A1, and PABP1, were shown to bind specifically to such elements in vitro (2,3,9,10,41). It is thought that the INS-binding factors may divert these mRNAs from the splicing route and promote their association with Rev, enabling their export and expression.…”
mentioning
confidence: 99%
“…Multiple purine-rich sequences named cis-repressive sequences or instability sequences (CRS/INS) were also identified in the genomic RNA (Schwartz et al 1992). These sequences are bound by hnRNP A1, polypyrimidine tract binding protein (PTB), poly(A)-binding protein (PABP), and polypyrimidine tract-binding protein-associated splicing factor (PSF) to regulate HIV-1 gene expression at the post-transcriptional level (Black et al 1996;Zolotukhin et al 2003). Tethering of other proteins such as the K homology splicing regulatory protein to HIV-1 RNA can also elicit RNA destabilization (Chou et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…99,102,105 Although the molecular mechanism by which INS-1 restricts HIV-1 mRNA translation initiation remains undefined, several reports suggest that host proteins are involved. [106][107][108][109] Along the same line, Brasey et al showed that the Gag ORF inhibited protein expression mediated by the HIV-1 5 0 UTR in the context of a HeLa cell line. 86 Such results were very puzzling at the time considering that the HIV-1 5 0 UTR drives the expression of Gag protein.…”
Section: Characterization Of Ires Sequencesmentioning
confidence: 90%